Side Effects of Combination Therapy with Epirubicin and Cyclophosphamide in Breast Cancer Patients at General Hospital Jend. Ahmad Yani Metro - Erdina, Erdina; Retno F, Na'imatul; Oentari , Octaviana Dyah (CV. Publikasi Indonesia, 2025)
Breast cancer is one of the most prevalent types of cancer globally, with a significant impact on women’s health. This study investigates the side effects of combination therapy with Epirubicin and Cyclophosphamide in breast cancer patients at General Hospital Jend. Ahmad Yani Metro. A retrospective cohort study was conducted using secondary data from medical records of 30 breast cancer patients who underwent chemotherapy with this combination therapy during June 2025. The study aimed to identify the onset and frequency of side effects associated with this chemotherapy regimen. The results showed that the most common side effects were hematologic (anemia) and non-hematologic (hair loss), with the onset of symptoms occurring at various stages of treatment. Data was analyzed using descriptive statistics, and findings were presented in frequency distribution tables to facilitate understanding of the side effects experienced by the patients. This study provides valuable insights into the challenges faced by breast cancer patients undergoing combination therapy, offering crucial information for improving patient care and management.